2022
DOI: 10.1111/polp.12498
|View full text |Cite
|
Sign up to set email alerts
|

Considered effective? How policy evaluations and threat perceptions affect support for surveillance in the context of terrorism

Abstract: Surveillance policies aimed at combating terrorism and improving public security can also lead to constraints on civil liberties. In view of this trade‐off between the potential benefits and risks of surveillance, it is particularly important to study how effectiveness considerations shape public support for surveillance. We argue that effectiveness perceptions enhance policy support, but that the manner in which citizens view policy effectiveness depends on their perceptions of threats related to terrorism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 62 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…In section three, the paper offers detailed analysis of citizen views of state surveillance in specific use cases. This enriches the statistical findings on general attitudes (e.g., Davis and Silver 2004), focusing on specific use cases in relation to online communication (see Christensen and Aars 2021;Degli Esposti, Ball, and Dibb 2021;Trüdinger and Ziller 2022).…”
Section: Research Findingsmentioning
confidence: 51%
See 2 more Smart Citations
“…In section three, the paper offers detailed analysis of citizen views of state surveillance in specific use cases. This enriches the statistical findings on general attitudes (e.g., Davis and Silver 2004), focusing on specific use cases in relation to online communication (see Christensen and Aars 2021;Degli Esposti, Ball, and Dibb 2021;Trüdinger and Ziller 2022).…”
Section: Research Findingsmentioning
confidence: 51%
“…The sociotechnical imaginaries in the findings contain further assumptions about governments and surveillance practices. As in Trüdinger and Ziller's (2022) research on German citizens, respondents hold assumptions about the effectiveness of social media surveillance by governments. The first group, for example, implicitly imagines that social media surveillance is effective at preventing terrorism and other violent events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have shown that respondents who perceived greater levels of threat from terrorism were less likely to support civil liberties (Davis and Silver 2004;Dietrich and Crabtree 2019) and more likely to support counterterrorism measures (Huddy et al 2005;Ziller and Helbling 2021). Studies on the German population have shown that being threatened by crime has a positive effect on acceptance of surveillance technologies (Trüdinger 2019;Van Heek, Arning, and Ziefle 2016). This lets me assume that the higher the threat, the greater the support for a policy (H1).…”
Section: Support For Surveillance Policiesmentioning
confidence: 99%
“…In this October 2022 issue of Politics & Policy ( P&P ) we offer a strong lineup of articles spanning an array of policy, public administration, and comparative international political issues. Trüdinger and Ziller (2022) add new insights from Germany to wider debates on the balance between security and civil liberties (see e.g., Doan & Schwarz, 2020; Jenkins‐Smith & Herron, 2009) in their article on policy effectiveness and public support for different kinds of counterterror surveillance policies. Fowler's (2022) excellent contribution tackles party polarization on environmental policy in the United States Congress (see also in P&P : Dunning, 2021; Gershtenson et al, 2006).…”
mentioning
confidence: 99%